Analisis Konsep Ketahanan Keluarga Pada Pengasuhan Single Father dan Dinamika Peran Ganda Ayah - Ghaisania Amanda; Aan Listiana; Yeni Rachmawati (Institut Agama Islam Negeri Madura, 2025)
This study discusses the analysis of the concept of family resilience in the care carried out by a single father due to divorce due to the death of the mother and describes the dynamics of the father's dual role. The purpose of this article is to provide new knowledge about family resilience carried out by single fathers in their care at home. Data collection was carried out by literature study analyzing scientific journals from reputable journals both nationally and internationally. The results show that aspects of family resilience (physical aspects, health aspects, social aspects, and psychological aspects) in single fathers have an impact on the father's parenting in raising children. Losing a mother figure affects the father's dual role in the family, both financial responsibility and childcare responsibility. The tendency of authoritarian, permissive, and situational parenting by single fathers with the help of parties of the opposite sex outside the nuclear family. The father's dual role in parenting also has an impact on the consequences of trauma on children such as cognitive or academic problems at school, social functioning, and attention deficits.